The Alphabetisation of Thought : Orthography, Locke, and Natural Philosophy - Isermann, Michael M. (Brill's Studies in Intellectual History., 2025)
The Alphabetisation of Thought is a bold and original study about the rise, spread and dominance of orthographic thinking in the Early Modern period. Starting out as a local, grammatical mode of thinking, it soon gained momentum, strength and depth, turning into a development that provoked a wholesale reorganisation of thought along the lines of alphabetical writing. The study brings together an unprecedented range of texts from areas as diverse as grammar, epistemology, classical scholarship, natural philosophy and cryptography. A major source of evidence is Locke's doctrine of ideas as laid out in his Essay Concerning Human Understanding . Echoing the orthographic debate of the preceding 150 years, it affords not only crucial insight into the final stages of the alphabetisation process, but also glimpses of its legacy.